New Face of International Law From Western to Global Construct - Atip Latipulhayat (Faculty of Law, Universitas Padjadjaran, 2020)
The modern international law, not only imitates, but the substance is truly the European values and traditions. The European nations produce the norm of international law with a clear objective is to divide the world into